The Application of Video Transcript on Youtube for Eight Grades Reading Literacy: A Survey Research - Aulia, Anggita Fitri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research was written to learn about the application of video transcripts from YouTube videos for students, especially in Reading Literacy. This research uses a Quantitative approach and a questionnaire survey method. The participants of this research were 30 students in 8th-grade Junior High School from Surabaya and Sidoarjo. The aim of this research for to know or compare whether the application of videos with presenting transcript text. The results of this research are that many students are interested in using Transcripts/subtitles when they watch YouTube videos. Therefore, their reading skills are additionally affected by this research. In addition to the video, they watch the text transcription on their device. Usually, they use Digital Apps like Wattpad, Dreame, Webtoon, etc., or use games and social media to support their reading literacy. This research indicated that video transcripts are not only utilized in educational circumstances but in general reading activities outside of the classroom as well.